Modelo de regressão logı́stica com mistura de distribuições : estimadores de máxima verossimilhança e bayesiano utilizando o Stan - Ferreira Junior, Luis Roberto (Universidade Federal de São Carlos, 2024)
We explore the logist regression model, estimating its parameters through maximum likelihood and Bayesian estimators. We use mixtures of distributions for 𝐾 = 1 and 2 components. The Hamiltonian Monte Carlo implemented in Stan is used to obtain the Bayesian estimates and R for the MLEs.
Logistic regression model with mixture of distributions : maximum likelihood and Bayesian estimators using Stan
Keywords: Regressão logı́stica; Modelo de mistura; Inferência bayesiana; Marketing; Logistic regression; Mixture model; Bayesian inference; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::PROBABILIDADE E ESTATISTICA APLICADAS